Spiritual Autobiography – A Contemporary Approach - Someșan, Grigore-Toma (Journal for the study of religions and ideologies, 2021)
Review of Iuliu-Marius Morariu, Landmarks of Spiritual Autobiography in the Orthodox Space of the 19th and 20thCenturies: John of Kronstadt, Silouan the Athonite and Nicolas Berdiaev [Repere ale autobiografiei spirituale din spațiul ortodox în secolele XIX și XX: Ioan de Kronstadt, Siluan Athonitul și Nicolae Berdiaev], (Iaşi: Editura Lumen, 2019).